Implementasi Teknologi Tepat Guna Spinner Peniris Minyak Sebagai Upaya Mengurangi Resiko Kesehatan di Desa Karangan Kabupaten Jombang - Danang Radistya; Anugrah Bayu Santoso; Eryan Okky Tegar Adinda; Dicko Maulana Yudha Batara; Mu’tasim Billah (Universitas Kristen Indonesia Toraja, 2023)
The use of cooking oil among the people is almost inseparable. people will tend to consume processed foods with oil. Sometimes the oil is not only used for frying, but is used as the main raw material in food. However, excessive use of cooking oil can stalk the health condition of the body. One way to reduce the oil contained in food is to use good appropriate technology. The oil slicing spinner used in the implementation of appropriate technology as an effort to reduce health risks in Karangan Village is by holding a spinner assembly. The results of the implementation of appropriate technology in the Karangan Village area by KKN-T Group 07 were that the tool was given to the PKK organization in Karangan Village. It is hoped that from this activity the people of Karangan Village will be able to find out the benefits of applying appropriate technology and be able to assemble independently which can later be used individually.